Flexural Strength Behaviour of Apa (Afzeliabipindensis) Reinforced Stabilized Lateritic Soil Beam - Philip Baki OZIGI; Lawrence Zahemen TULEUN; Alao Abdullahi JIMOH (Institute of Research and Community Outreach - Petra Christian University, 2020)
This paper reports on the flexural strength behaviour of Apa reinforced stabilized lateritic soil beams. The potential of using timber as a reinforcement material is because timber is abundant, cheap and locally available compared to conventional steel. Apa timber possess a tensile strength of 68.34 N/mm2. Experimental and Finite Element Analysis using ANSYS 15 were carried out to determine the flexural strength of Apa reinforced lateritic soil beams. The results showed an increase in the load-bearing capacity with increase in the percentage area of Apa reinforcement used in Lateritic soil beams. BS 8110-1:1997 requires that area of reinforcement for beams should not exceed 4%. At 4 percent area, the flexural strength of the Apa reinforced lateritic soil beams (ALB) was 0.763 N/mm2 with corresponding load capacity of 3.435 kN which is slightly higher than the steel reinforced lateritic soil beams (SLB) of 0.740 N/mm2 with corresponding load capacity of 3.329 kN obtained in the report